Clinical and pathological kidney aspects of sickle cell anemia at Dakar: study of 11 cases of renal biopsies - Ka, EF; Fall, S; Cissé, MM; Dial, C; Berrada, H; Keita, I; Tall, AO; Niang, A; Ndiaye, FSD; Diouf, B (African Journal of Nephrology, 2014)
Few studies are devoted to the practice of renal biopsy in sickle cell nephropathy; our objective was to determine the histological and evolutionary patterns of renal lesions in sickle cell patients who underwent renal biopsy in Dakar. Methods:This was a retrospective multicentric study (conducted from December 2009 to August 2011) on renal biopsies performed on sickle cell anaemic patients at the Nephrology Department of Teaching Hospital Aristide Le Dantec and the Albert Royer Childrens Hospital. The histological, therapeutic and evolutionary data were analysed. From the 292 total renal biopsies, 11 (3.80%) were performed on sickle cell patients (6SS, 1SBth + 4 AS) with a mean age of 23.1 [13-51 years]. Nephrotic syndrome was the indication of renal biopsy in all cases. Focal segmental glomerulosclerosis was the most frequent histological finding (five cases), followed by a combination of various specific lesions (hypertrophy of glomerular and peritubular capillaries), minimal glomerular lesions (three cases), membranoproliferative glomerulonephritis (two cases) and extra-membranous glomerulonephritis (one case). Complete remission after treatment was achieved in seven cases and one patient expired. Three patients did not continue with follow-up appointments. Conclusions:Renal biopsy is not very frequent in the course of sickle cell anaemia and in most cases it is performed because of nephrotic syndrome. The histological findings are diverse with a predominance of focal segmental glomerulosclerosis.